Antimicrobial effect of natural extracts obtained from plant material - Šilha, David; Csánová, Magdaléna; Vacková, Barbora; Šilhová, Lucie (Lubelskie Towarzystwo Wspierania Nauk Farmaceutycznych, 2017)
Recently, medical plants and their extracts have gained importance as potential antibacterial agents. Secondary metabolites of plants including tannins, flavonoids and alkaloids have been found to possess antimicrobial properties in vitro. A possible natural alternative to chemical-based bactericides is the use of plant extracts. We tested several plant extracts against these pathogenic bacteria, e.g. extracts from anise, star anise, clove, juniper, nutmeg, cinnamon, then celery, celery stem, red cabbage, red beet, pine needles, spruce needles and rose hip.
Antimikrobiální efekt příroních extraktů získaných z rostlinných materiálů
Keywords: natural extracts; plant material; inhibition; přírodní extrakty; rostlinné materiály; inhibice